Ki-67 Expression and Histopathological Type, Metastatic Status, and Risk Factors in Lung Cancer - Muhammad Khairani; Sri Melati Munir; Darmawi Darmawi; Indra Yovi; Indi Esha; Zarfiardy Aksa Fauzi; Zahtamal Zahtamal (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Lung cancer remains a leading cause of cancer-related morbidity and mortality worldwide. In Indonesia, the incidence and death rates associated with this disease remain alarmingly high. Ki-67 is a potential biomarker for assessing cellular proliferation and metastatic potential. However, its clinical application in lung cancer remains inconsistent. This study aimed to analyze the association between Ki-67 expression and histopathological subtype, metastatic status, and clinical risk factors in patients with lung cancer. Methods: This study enrolled 42 patients diagnosed with lung cancer at Arifin Achmad General Hospital, Pekanbaru, Indonesia. Statistical analysis used the Chi-square or Fisher’s exact test (non-parametric tests) for categorical data and the Kolmogorov-Smirnov test, depending on the data characteristics. Participants were selected based on predefined inclusion criteria, complete medical documentation, and available Ki-67 immunohistochemistry results. Results: Among the 42 patients analyzed, 34 (80.9%) exhibited metastasis. The findings revealed a significant correlation between Ki-67 expression and metastasis (p=0.0038), whereas no significant associations were observed with age, sex, smoking status, or histopathological classification. Most patients (approximately 69%) had low Ki-67 expression. Conclusion: Ki-67 expression was associated with metastatic status in patients with lung cancer and might serve as a prognostic biomarker. Further studies with larger sample sizes are needed to validate these findings.